Comparison of Adult Education Policies in Turkey and European Union - Aksakal, Bunyamin; Kazu, Ibrahim Yasar (Elsevier Science Bv, 2015)
The lifelong learning a reality by the European Commission defines lifelong learning as all learning activities undertaken throughout life, with the aim of improving knowledge, skills and competences within a personal, civic, social and/or employment-related perspective. The aim of this article is to review the effect of factors that cause globalisation on behalf of education and inter-cultural relations within the context adult education between Turkey and European Union Countries. In addition, the effects of globalization on adult education are considered through making conceptual analysis of the social change in educational concept. (C) 2015 The Authors. Published by Elsevier Ltd.
Global Conference on Contemporary Issues in Education (GLOBE-EDU 2014) -- JUL 12-14, 2014 -- Las Vegas, NV
Keywords: Education; adult and continuing education; European Union; lifelong learning